Keterlibatan Pemakai, Kemampuan Teknik Personal, Ukuran Organisasi dan Kinerja Sistem Informasi Akuntansi - Wiratmaja, Kadek Satria; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
This study aims to determine the effect of user involvement, personal technical ability and organizational size on the performance of accounting information systems in East Denpasar LPD. Samples were taken based on purposive sampling technique as many as 12 Village Credit Institutions. Respondents in this study were the directors and the head of the accounting department. Data was collected by means of a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that user involvement and personal technical skills had a positive effect on the performance of accounting information systems. Organizational size does not have a positive effect on the performance of accounting information systems. This shows that user involvement and personal technical skills greatly support the performance of accounting information systems to work optimally. Keywords: User Involvement; Personal Technical Ability; Organizational Size; Accounting Information System Performance.